Morbidity trend of lip cancer in Podkarpacie and in Poland in the years 1963–2013 - Gawełko, Jan; Cierpiał-Wolan, Marek; Podgórska-Bednarz, Justyna; Kawecki, Andrzej (European Journal of Clinical and Experimental Medicine, 2017)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The dramatic decline in the incidence of lip cancer, which until the 80s of the twentieth century was the cause of significant morbidity, is an example of changes in the structure and trends of cancer incidence both in Poland and in the regions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. Therefore, the aim of this paper is to analyze the changes in the morbidity trend of the lip cancer during the last 50 years, both in Poland and in Podkarpacie. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A retrospective analysis of the lip cancer morbidity in the Podkarpackie region and in Poland in the years 1963–2013 was carried out based on data from the literature and our own research. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results and conclusion. A steady decline in the incidence of lip cancer in Podkarpacie has been observed since 1982 for men and 1983 for women. In Poland these trends have been observed since 1972 for men and 1993 for women. In the analyzed period significant changes in the incidence structure in terms of sex are observed – from approximately 1:10 (women / men) in 1963 similarly in Podkarpackie and Poland – to 1:4.6 in Podkarpacie and 1: 2.6 in Poland in 2013.